Serial Mediation Roles of Perceived Stress and Depressive Symptoms in the Association Between Sleep Quality and Life Satisfaction Among Middle-Aged American Adults - Yang, Yanxu; Cuffee, Yendelela L.; Aumiller, Betsy B.; Schmitz, Kathryn; Almeida, David M.; Chinchilli, Vernon M. (Frontiers in Psychology, 2022)
In this study, we used data from the second wave of Midlife in the United States (MIDUS) Study, MIDUS Biomarkers and MIDUS 3. We applied the serial mediation model to explore the serial mediating effects of perceived stress and depressive symptoms on the relationship between sleep quality and life satisfaction. A total of 945 participants were included in our study. The total indirect effect of sleep quality on life satisfaction through perceived stress, depressive symptoms and the combination of perceived stress and depressive symptoms accounted for within the overall model was 45.5%. At the intervention level, programs designed to improve the level of life satisfaction among adults should focus on perceived stress and depressive symptoms. The prevention of perceived stress and depression contributes to improving life satisfaction and well-being. The serial mediation results should be confirmed by further longitudinal study.